Bibliometric analysis: Root and root canal morphology using cone‐beam computed tomography - Mohmed Isaqali Karobari; Beenish Fatima Alam; Raima Bashir; Muhammed Faisal Fahim; Mubashir Baig Mirza; Tahir Yusuf Noorani (Wiley, 2023)
Abstract Objectives This bibliometric analysis aimed to evaluate the leading nations, authors, journals, institutes, highly cited publications, and most commonly used keywords concerning scientific publications based on root and root canal morphology using the CBCT. Material and Methods For this bibliometric analysis, an extensive search was carried out on September 25, 2023 using the Scopus database. Pertinent articles in the field were scrutinized after applying inclusion and exclusion criteria. Data were evaluated using Vosviewer and Microsoft Excel. Results A literature search revealed the initiation of scientific publication in 2008. Significant contributions made by Saudi Arabia, India, and China concerning the number of publications were seen. Similarly, Jazan University from SA was recognized as the leading institute. The Journal of Endodontics was the leading journal, while authors JNR Martins and G Gambarini produced the highest number of papers. Conclusions This bibliometric analysis demonstrated that scientific publications have increased tremendously since 2008. Significant contributions have been made by developing and developed nations. The Journal of Endodontics and Jazan University have been identified as the leading journal and institute.